Politics in rice producing irrigated area in Northeastern Iloilo (Barotac Nuevo-Pototan Area) - Bajade, Ian Louie V.
This research project is an exploratory study which determines the power relations among individuals, groups, groupings and entities involved in rice production process in rice producing irrigated area of Northeastern Iloilo. This study was conducted in the barangays Of Tabucan and Canilauan of Barotac Nuevo and Tuburan and Toncom Ilaud of Pototan using interviews with respondents and selected key informants and secondary data taken from the records of the Municipal Agrarian Reform Office, local government units, Philippine National Police blotter and farmers' organization of the locale of the study as sources of information of this research project. It was found out that: (1)there is a three level class structure in the locale of the study; (2) the three level class structure leads to a corresponding three level power relations among individuals inside the realm of rice production process; (3) the tenurial arrangements solely determines the distribution of productivity among individuals and entities involve in rice production and (4) the tenants are biggest class of exploiters in the production process brought about by the widespread practice of sub-tenurial arrangement-pamorsyento which makes the tenants "ersatz landlord" and exploiters of the nagapamorsyento-farm laborer., Tracing the flow of politics in rice producing irrigated area, it was found that the tenurial arrangement gives shapes to the power relations in the locale of the study.